Physiological Synchrony of the Broad Bean Weevil, Bruchus rufimanus Boh., to the Host Plant Phenology, Vicia faba L. - Hamidi, Rachid; Taupin, Pierre; Frérot, Brigitte (Frontiers in Insect Science, 2021)
The aims of the study were to understand the physiological and phenological relationship between Bruchus rufimanus and V. faba in the perspective of IPM strategies. V. faba, an important food resource for humans and livestock is the main host plant of B. rufimanus. Adults feed on the pollen, females lay eggs on pods, and larvae develop into the seeds. Pending the blooming phase, the weevil may feed on the pollen from wild plants. Depending on the sowing date, the phenological time lag should lead the plant parts, most utilized by the weevil, less or more available during the key life stages of the pest. The aims of the study were therefore (1) to assess the impact of the sowing date (i.e., cultivars) on the phenological relationship between B. rufimanus and V. faba, and (2) to identify alternative pollen resources during the vegetative phase. Insects were collected weekly on two cultivars: winter-sown and spring-sown fields. Ovarian development, fecundity and diet were monitored using dissected adults. Results showed that immature adults colonized the blooming winter-sown field and then two weeks later, the blooming spring-sown field. Sexual maturity of the weevils is related with V. faba pollen consumption. The sexual maturity of females increased with the growing density of flowers and the first pods were quickly covered with eggs. In spring-sown field, first pods grew 19 days later, while collected females in winter sown field had already laid most of their eggs. Feeding tests were carried using flowers collected from plants growing close to the fields: wild chervil, oilseed rape and wild Prunus. All this pollen were consumed by the weevils. The study showed a perfect synchrony between the host and the pest. Late sowing date and control of the early blooming wild plants surrounding the crops might reduce the attacks in field beans. More broadly, the study helps to understand the eco-ethology of the insect in cultivated areas.